2013
DOI: 10.1186/1477-7827-11-112
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis fertility index score maybe more accurate for predicting the outcomes of in vitro fertilisation than r-AFS classification in women with endometriosis

Abstract: BackgroundEndometriosis is a common disease. The most widely used staging system of endometriosis is the revised American Fertility Society classification (r-AFS classification) which has limited predictive ability for pregnancy after surgery. The endometriosis fertility index (EFI) is used to predict fecundity after endometriosis surgery. This diagnostic accuracy study was designed to compare the predictive value of the EFI with that of the r-AFS classification for IVF outcomes in patients with endometriosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
2
19
0
4
Order By: Relevance
“…It should be considered that in our study ART was offered only after 1 year of childbearing time and the disease might have progressed in the meantime. On the other hand, similar findings were obtained by Wang et al [21] that offered an ART cycle 6 months after the laparoscopic treatment supporting the idea that this aspect is probably not critical for the general validity of the score. Therefore, this information allows the possibility of providing a more complete counseling at the time of decision making.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It should be considered that in our study ART was offered only after 1 year of childbearing time and the disease might have progressed in the meantime. On the other hand, similar findings were obtained by Wang et al [21] that offered an ART cycle 6 months after the laparoscopic treatment supporting the idea that this aspect is probably not critical for the general validity of the score. Therefore, this information allows the possibility of providing a more complete counseling at the time of decision making.…”
Section: Discussionsupporting
confidence: 75%
“…The best cut-point for pregnancy based on sensitivity and specificity was 5.5. This result, obtained on a small number of patients, has been recently confirmed by Wang et al [21]. This study was conducted on 199 women with endometriosis who received IVF treatment after surgery demonstrating that EFI score was a predictive tool of IVF outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…However, it has limited ability for predicting a successful pregnancy after surgery [11]. Opoien et al [15] reported on the r-ASRM classification of endometriosis and the pregnancy rate with ART due to tubal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the relationship between EFI and ART outcomes was reported [11]. EFI was suggested to have greater predictive power than the r-ASRM for a successful pregnancy with ART in endometriosis patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [53] were the first to compare the predictive value of the EFI score with the r-ASRM classification in the same population of women with endometriosis who had received IVF treatment. They suggested that neither the future of pregnancy nor IVF outcome could be predicted by r-ASRM classification.…”
Section: New Scoring System For Infertilitymentioning
confidence: 99%